Red pedagógica de acciones lenguas y de aclimatación a las culturas (REPALAC): un camino hacia la cohesión social, la ética ciudadana y la paz (Educational Perspectives Magazine (REPED), 2022)
The third millennium with all its globalise frenzy compels us to measure the angle separating the difference of level, more and more visible, between the knowledge and the knowledge-being. Starting from that, it’s important to sketch wills in order to minimize this distance, deploying joint pedagogies that permit to approach autonomies, commons participations, and an awareness of the “planetary citizenship” ffom Edgar Morin.The cultural diversity can transform itself in a powerful bridge of creativity and human growth or on the contrary, it can lead to social tensión. The Chilean school is changing because it’s opening to children and youth people issued from migration, descendents from African people or from others cultural minorities. The execution of intercultural education is therefore, the challenge and the response to the educative complexity in our time.The Pedagogic Net of Languages Actions and Acclimation to the Cultures (REPALAC) represents at the same time, a suggestion for the teachers who are working in multicultural sectors and also a didactic based on the interaction among all the actors, on the priority gived to the process, to the educative product, to the context, to the impact, to the Creative development and to the critical circle reflection, in other words it’s a bio didactic.